Getting the control across: Control transmission in information systems offshoring projects. (15th August 2017) - Mähring, Magnus; Wiener, Martin; Remus, Ulrich
Abstract: Offshoring of information systems (IS) projects has become a widespread global practice. While prior research suggests that controlling, and communicating with, offshore vendors represent key managerial challenges, the topic of how control is communicated, or transmitted, from client to vendor has been widely neglected. Our study focuses on control transmission in the critical relationship between client and offshore vendor managers, and its impact on the performance of IS offshoring projects. Drawing on a matched‐pair survey with 172 client and vendor managers from 86 projects, our results provide several new insights to the IS literature: First, we find that both behaviour and outcome control have the capacity to be transmitted consistently in lateral IS offshore project relationships. Second, our results show that consistent transmission translates into a performance effect only for outcome control. Third, we find that high‐performing offshore projects are characterized by both greater control transmission consistency and greater use of outcome control compared to low‐performing projects. In sum, our study extends theory on IS project control by highlighting that effective control of IS offshoring projects is not only about selecting proper controls but also about ensuring that, as a controller, you get the control across to the controllee.